Cloverleaf plasma cell nuclei in multiple myeloma - Mahjouba Baiya; Hicham Yahyaoui; Ibtissam Mhirig; Imane El Khannouri; Mustapha Ait Ameur; Mohamed Chakour (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2022)
A 65-year-old man was diagnosed with multiple myeloma (IgG-Lambda) and was treated with high-dose dexamethasone as induction therapy followed by thalidomide-based regimens. About 18 months after the initial diagnosis, the patient presented a first relapse which was treated with the LCD protocol (Lenalidomide, Cyclophosphamide, Dexamethasone).